Neural processing of the own child’s facial emotions in mothers with a history of early life maltreatment - Neukel, Corinne; Herpertz, Sabine; Zietlow, Anna-Lena; Fuchs, Anna; Möhler, Eva; Bertsch, Katja (European archives of psychiatry and clinical neuroscience, 2019)
Early life maltreatment (ELM) has long-lasting effects on social interaction. When interacting with their own child, women with ELM often report difficulties in parenting and show reduced maternal sensitivity. Sensitive maternal behavior requires the recognition of the child’s emotional state depicted in its facial emotions. Based on previous studies, it can be expected that ELM affects the neural processing of facial emotions by altering activation patterns in parts of the brain’s empathy and mentalizing networks. However, so far studies have focused on the processing of standardized, adult facial emotions. Therefore, the current study investigated the impact of ELM on the processing of one’s own child’s facial emotions using functional magnetic resonance imaging. To achieve this, 27 mothers with and 26 mothers without a history of ELM (all without current mental disorders and psychopharmacological treatment) took part in an emotional face recognition paradigm with happy, sad, and neutral faces of their own and an unknown primary school-aged child of the same age and sex. We found elevated activations in regions of the mentalizing (superior temporal sulcus, precuneus) and mirror neuron (inferior parietal lobule) networks as well as in the visual face processing network (cuneus, middle temporal gyrus) in mothers with ELM compared to the non-maltreated mothers in response to happy faces of their own child. This suggests a more effortful processing and cognitive empathic mentalizing of the own child’s facial happiness in mothers with ELM. Future research should address whether this might indicate a compensatory recruitment of mentalizing capacities to maintain maternal sensitivity.
Published online: 28 July 2018
Gesehen am 05.07.2019